Patient satisfaction with participation in a randomized exercise trial: Effects of randomization and a usual care posttrial exercise program. (December 2013) - Courneya, Kerry S; Forbes, Cynthia C; Trinh, Linda; Sellar, Christopher M; Friedenreich, Christine M; Reiman, Tony
Background: Participation in an exercise trial is a major commitment for cancer survivors, but few exercise trials have evaluated patient satisfaction with trial participation. Purpose: To examine patient satisfaction with participation in the Healthy Exercise for Lymphoma Patients (HELP) Trial and to explore possible determinants. Methods: The HELP Trial randomized 122 lymphoma patients to 12 weeks of supervised aerobic exercise training (AET; n = 60) or to usual care (UC; n = 62), with the option of participating in a 4-week posttrial exercise program. At the 6-month follow-up assessment, participants evaluated their overall trial satisfaction. Results: Personal satisfaction with trial participation was strongly influenced by group assignment with participants randomized to AET reporting participation to be more rewarding (p < 0.001) and personally useful (p < 0.001) than participants randomized to UC. UC participants who completed the optional 4-week posttrial exercise program reported participation to be more rewarding (p = 0.008) and personally useful (p < 0.001) than UC participants who declined the program. Limitations: The study is limited by the lack of a validated measure of participant satisfaction, and the fact that the offer of participation in the posttrial exercise program to the UC group was not randomized. Conclusions: Lymphoma patients randomized to UC viewed it as less rewarding and personally useful despite being offered a 4-week posttrial exercise program. UC participants who completed the 4-week program reported personal satisfaction levels similar to the AET group; however, the causal direction of this association is unknown. Researchers should continue to evaluate participant satisfaction in exercise trials.